SIMULASI KINERJA SKEA DI KABUPATEN TIMOR TENGAH SELATAN MENGGUNAKAN WAsP - Ibrochim, Malik (Indonesian Journal of Aerospace, 2010)
The analysis towards the performance of wind turbin simulation has been done in the District of Timor Tengah Selatan, Nusa Tenggara Timur Province by using the method of WAsP simulation. The data used as the simulation input are the wind speedand direction observed in Oelbukbuk vector map of TTS District and 3 (three) brands of 600kW wind turbin. The result shows that the performance of NEG-MICON wind turbine type NM 600-48 brand is better than 2 other brands (Vestas type V44 and Bonus type MKIV) that were simulated based on the wind climate and topography condition at TTS District NTT Province. Based on CF value, NEG-MICON type NM 600-48 wind turbine is 44,27 %, bigger than 2 other brands.